Analisis Pengaruh Pertumbuhan Ekonomi, Pendapatan Asli Daerah dan Alokasi Anggaran Belanja Modal Terhadap Indeks Pembangunan Manusia di Kota Banda Aceh - Nasir; Yuslinaini; A. Hamid; Zulfan Yusuf; Zakaria (Jurnal EMT KITA, 2023)
This study aims to look at the effect of economic growth, regional own-source revenue, and capital expenditure budget allocation on the rate of Human Development Index in Banda Aceh City for the 2010-2022 period. This study uses a quantitative method with data sources from the Badan Pusat Statistik Kota Banda Aceh. Data analysis through multiple linear regression using the SPSS program. The results showed that the variables Economic Growth and Regional Original Income had a positive and significant effect on the Human Development Index Rate in Banda Aceh City for the 2010-2022 period. Meanwhile, the Capital Expenditure Budget Allocation variable has a positive but not significant effect on the Human Development Index Rate in Banda Aceh City for the 2010-2022 period. The R value obtained was 0.825 indicating that the correlation or relationship between the dependent variable and the independent variable was 82.5%. The R2 value obtained was 0.681 which means that the quality of human development can be explained by economic growth, PAD, and capital expenditure budget allocation of 68.1%. While the remaining 31.9% is explained by other variables not included in this study.